ANTIMICROBIAL STEWARDSHIP IN HIGH-COMPLEXITY UNITS: INTERPROFESSIONAL ROLES, IMPLEMENTATION BARRIERS, AND IMPACTS ON PATIENT SAFETY - de Araújo, Luciane Margalho; de Sousa, Leidiane Braz; Cardoso, Leidson Frank Santana; Pires, Patrícia Gabrielly da Silva; Mendes, Marcus Corrêa; Correa, Amanda Emanuele dos Santos; de Almeida, Bruno Nunes; Nascimento, Isabela de Almeida; Lopes, Jander Marcus Cirino; Lanes, Deivid Junio Guilherme De; Belém, Wilson Santana Jovino; Carretilha, Arilana de Jesus; et al. (Seven Editora, 2025)
Antimicrobial resistance is one of the most pressing challenges for patient safety, especially in high-complexity hospital settings where antimicrobial use is frequent and clinical risk is elevated. Antimicrobial Stewardship Programs (ASPs) have emerged as essential strategies to promote appropriate antimicrobial use, reduce adverse events, and improve clinical outcomes. This narrative review analyzed 12 studies addressing interprofessional roles, organizational barriers, and the clinical impact of ASPs in critical care environments. Findings indicate that program effectiveness is directly linked to the integrated participation of multiple professional categories, highlighting the clinical pharmacist’s role in therapeutic optimization, nursing’s role in monitoring and patient safety, and the microbiologist’s contribution to evidence-based decision-making. Structured communication, interprofessional rounds, and continuous multiprofessional education were identified as key elements for strengthening ASP implementation. Cultural, structural, and communicative barriers, however, remain significant challenges. It is concluded that reinforcing collaborative culture, valuing interprofessional competencies, and investing in educational strategies are essential to ensure the sustainability and positive impact of ASPs in high-complexity units. DOI: https://doi.org/10.56238/sevened2025.037-044